REVIEWS (New blackfriars, 1971)
Reviews in the article THE CHRISTOLOGY OF EARLY JEWISH CHRISTIANITY by Richard N. Longenecker ARGUMENTS FOR THE EXISTENCE OF GOD, by J. H. Hick. THE WAY OF TRANSCENDENCE. Christian Faith without Belief in God, by Alistair Kee. LOGICO-LINGUISTIC PAPERS, by P. F. Strawson. ETHICAL KNOWLEDGE. by Joel J. Kuoaerman. CULTURE AND ANARCHY: AN ESSAY IN POLITICAL AND SOCIAL CRITICISM, by Matthew Arnold. edited by Ian Greaor. THE PENTECOSTAL MOVEMENT IN THE CATHOLIC CHURCH, by Edward D. O'Connor, C.S.C. CONSCIOUSNESS AND FREEDOM, by Pratima Bowes. THE NEW TESTAMENT CHRISTOLOGICAL HYMNS, by Jack T. Sanders